2008
DOI: 10.1111/j.1462-2920.2008.01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread distribution of a unique marine protistan lineage

Abstract: SummaryUnicellular eukaryotes (protists) are key components of marine food webs, yet knowledge of their diversity, distributions and respective ecologies is limited. We investigated uncultured protists using 18S rRNA gene sequencing, phylogenetic analyses, specific fluorescence in situ hybridization (FISH) probes and other methods. Because few studies have been conducted in warm water systems, we focused on two Atlantic subtropical regions, the Sargasso Sea and the Florida Current. Cold temperate waters were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 45 publications
6
69
0
Order By: Relevance
“…The size of these organisms has been the subject of recent discussion, with related sequences obtained from cells in the nanoplankton size range (2-20 mm). These larger 'biliphytes' were found in greater abundance (28% of all protist clones) in tropical eddy-influenced surface waters (Cuvelier et al, 2008). Our single-cell sequencing-based analysis indicates that biliphytes comprised a significant fraction of small protists in the studied sample from the Gulf of Maine.…”
Section: Discussionmentioning
confidence: 81%
“…The size of these organisms has been the subject of recent discussion, with related sequences obtained from cells in the nanoplankton size range (2-20 mm). These larger 'biliphytes' were found in greater abundance (28% of all protist clones) in tropical eddy-influenced surface waters (Cuvelier et al, 2008). Our single-cell sequencing-based analysis indicates that biliphytes comprised a significant fraction of small protists in the studied sample from the Gulf of Maine.…”
Section: Discussionmentioning
confidence: 81%
“…Our previous study showed that picobiliphytes are prevalent in eutrophic waters (Cheung et al, 2008), and this finding is supported by the results obtained in this study (Figure 1). The repeated recovery of picobiliphytes in our samples also provides further evidence on their prevalence in subtropical waters (Cheung et al, 2008, Cuvelier et al, 2008. NAGIII, a newly defined alveolates group, contains environmental sequences from oceanic and coastal waters .…”
Section: Diversity Of the Picoeukaryotic Assemblagesmentioning
confidence: 84%
“…The paucity of cultured picophytoeukaryotes from this and other divisions is a major restriction on physiological and ecological research on photosynthetic picoeukaryotes. We also know there are lineages for which there is not a single cultured representative (e.g., Not et al 2007b;Cuvelier et al 2008), these will be discussed in later sections.…”
Section: Photoautotrophsmentioning
confidence: 99%